Effect of pH on calcite growth at constant aCa2+/aCO32- ratio and supersaturation - Ruiz-Agudo, E.; Putnis, Christine; Rodriguez-Navarro, C.; Putnis, Andrew (2011)
In situ Atomic Force Microscopy (AFM) was used to study the growth of calcite at a constant supersaturation (O=6.5) and solution stoichiometry (aCa2+/aCO32-=1) in the pH range 7.5-12. The calcite growth rate decreased with increasing pH in the studied range. The results can be successfully explained by the surface complexation model for calcite growth and by considering the effect of OH- ions on solute hydration. At pH below 8.5, growth occurs mainly by CaCO30 incorporation at >CaHCO30 surface sites. CaCO30 should be more easily incorporated than free Ca2+ ions, as water exchange is usually faster if water molecules in the ion hydration shells are substituted by other ligands, as in CaCO30. However, at pH above 9, Ca2+ incorporation at >CaHCO30 sites also contributes to calcite growth as a result of the increased frequency of water exchange in calcium hydration shells due to the presence of strongly hydrated OH-. This also leads to an increase in the solid-liquid interfacial tension at high pH, which seems to reduce the nucleation rate and increase the average size of crystals precipitated in macroscopic, non-seeded experiments. The reduction of calcite growth rate is a consequence of decreasing surface concentration of active growth sites (i.e., >CaHCO30) with increasing pH under our experimental conditions. Changes in two-dimensional island morphology were observed at high pH (12), possibly due to the stabilization of polar scalenohedral faces by the presence of OH- ions. This work may help to improve our understanding of the effects of carbonate-solution reactions resulting from potential changes in the pH of the oceans and surface waters in response to variations in atmospheric CO2, as well as in understanding calcite precipitation in highly alkaline environments both natural (e.g., alkali lakes) and artificial (e.g., cement carbonation). © 2010 Elsevier Ltd.